2015
DOI: 10.4269/ajtmh.14-0842
|View full text |Cite
|
Sign up to set email alerts
|

Intraventricular Taenia solium Cysts Presenting with Bruns Syndrome and Indications for Emergent Neurosurgery

Abstract: Abstract. Bruns syndrome is an unusual phenomenon, characterized by attacks of sudden and severe headache, vomiting, and vertigo, triggered by abrupt movement of the head. The presumptive cause of Bruns syndrome is a mobile deformable intraventricular mass leading to an episodic obstructive hydrocephalus. Intraventricular tumors have been associated with Bruns syndrome; however, few cases of intraventricular neurocysticercosis have been reported to present with Bruns syndrome. We report the first series of fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…We also conducted a literature review looking for reported cases with surgical/ histopathological confirmation of ventricular cysticercosis during the past 20 years. A total of 21 papers describing 29 patients, where case descriptions and neuroimaging findings were appropriately detailed as to apply our set to diagnostic criteria, were found [35,37,[56][57][58][59][60][61][62][63][64][65][66][67][68][69][70][71][72][73][74]. Despite the fact that most of these patients did not had a serum EITB performed, the set allowed a definitive pre-operative diagnosis of NCC in 23 cases (one absolute criterion in 12, two major neuroimaging in six, and one major neuroimaging plus one confirmative in five), and a probable diagnosis in the remaining six patients.…”
Section: Additional Evaluationsmentioning
confidence: 99%
“…We also conducted a literature review looking for reported cases with surgical/ histopathological confirmation of ventricular cysticercosis during the past 20 years. A total of 21 papers describing 29 patients, where case descriptions and neuroimaging findings were appropriately detailed as to apply our set to diagnostic criteria, were found [35,37,[56][57][58][59][60][61][62][63][64][65][66][67][68][69][70][71][72][73][74]. Despite the fact that most of these patients did not had a serum EITB performed, the set allowed a definitive pre-operative diagnosis of NCC in 23 cases (one absolute criterion in 12, two major neuroimaging in six, and one major neuroimaging plus one confirmative in five), and a probable diagnosis in the remaining six patients.…”
Section: Additional Evaluationsmentioning
confidence: 99%
“…The antihelminthic drug of choice is albendazole, which is superior to praziquantel because it does not interact pharmacologically with glucocorticoids and antiepileptic drugs. 2,7 In a review of the PubMed database with the MeSH terms neurocysticercosis AND Bruns syndrome, eight publications of Bruns syndrome caused by neurocysticercosis were found, totalizing 16 cases. Headache was the main symptom reported (15 cases), followed by vomiting (9), confusion (3) and vertigo (3).…”
Section: Discussionmentioning
confidence: 99%
“…It is characterized by a transient increase in intracranial pressure, caused by a floating mass in the ventricular system, producing hydrocephalus and leading to episodes of headache, vertigo and vomiting, which are triggered by sudden head movements. 1,2 The authors report the case of a patient who presented Bruns syndrome due to neurocysticercosis. A review of the published cases is discussed in the present article.…”
Section: Introductionmentioning
confidence: 99%
“…In patients with ventricular cysts, these may directly occlude the foramens of Monro, Luschka, Magendie and the cerebral aqueduct . A particularly common form of intracranial hypertension in NCC is Brun's syndrome, characterized by the abrupt onset of symptoms associated with brisk changes in the position of the head, following the obstruction of the CSF flow through the cerebral aqueduct by freely floating cysts in the IVth ventricle .…”
Section: Clinical Manifestations Of Nccmentioning
confidence: 99%